PENDAMPINGAN PENYUSUNAN DIGITALISASI AKUNTANSI PADA UMKM DI SENTOLO - Laila Putri Khairunnisa; Hasim As'ari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This activity aims to improve the ability of MSME owners in Sentolo to prepare digital-based financial records. The methods applied in this activity include training and direct assistance for participants. The training was conducted to provide understanding regarding the importance of accounting digitalization, while the mentoring aimed to help participants practice the use of digital financial recording applications directly. The results of the activity showed that MSME owners who previously used simple bookkeeping were able to carry out financial recording in a more structured, systematic, and organized manner. The use of digital applications helped participants record transactions, monitor business financial conditions, and prepare simple financial reports more easily. In addition, this training also increased business owners’ awareness of the importance of separating personal and business finances. Therefore, accounting digitalization assistance can serve as an effective solution for improving the quality of MSME financial management in a sustainable manner.